High-dose Factor XIII administration induces effective hemostasis for trauma-associated coagulopathy (TAC) both in vitro and in rat hemorrhagic shock in vivo models - Nagashima, Futoshi; Inoue, Satoshi; Koami, Hiroyuki; Miike, Toru; Sakamoto, Yuichiro; Kai, Keita (The journal of trauma and acute care surgery, 2018)
Trauma-associated coagulopathy (TAC) is an early and primary complication in severe trauma patients. Factor XIII (FXIII) is reported to stabilize a clot in the late phase of the coagulation cascade. The goal of this study was to investigate whether the administration of FXIII improves the condition of TAC both in vitro and in vivo. We evaluated the effects of different doses, including a very high dose of FXIII (3.6-32.4 IU/mL) on tissue-plasminogen activator-induced hyperfibrinolysis and the combined condition of dilutional coagulopathy and tissue-plasminogen activator-induced hyperfibrinolysis in vitro. The coagulation status was analyzed by rotational thromboelastometry (ROTEM) and Sonoclot. Then, we evaluated the effect of high-dose FXIII (300 IU/kg) for severe coagulopathy in vivo using a rat liver trauma model in which coagulopathy similar to TAC was observed. Survival time and the amount of intra-abdominal bleeding of rats were measured, and a coagulation test was also performed. Histologic evaluations of rats' lung and kidney after FXIII administration were completed. High-dose FXIII significantly improved clot strength as well as increased resistance to hyperfibrinolysis in vitro which was confirmed by ROTEM. Platelet function on Sonoclot was significantly increased by FXIII in a dose-dependent manner. Factor XIII significantly decreased the total amount of bleeding and prolonged the survival time compared to control (control vs FXIII: 108.9 ± 11.4 vs 32.6 ± 5.5 mL/kg; p < 0.001; 26.0 ± 8.8 vs 120 minutes, p < 0.001) in a rat model. Rotational thromboelastometry parameters and platelet function on Sonoclot were significantly improved in the FXIII (+) group compared to control. No adverse effects of FXIII were detected histologically. Factor XIII not only generated stable clot resistance to hyperfibrinolysis but also enhanced platelet function by facilitating clot retraction. High-dose FXIII administration therapy has significant clinical impact for severe trauma accompanied with TAC. Human in vitro and rat in vivo experimental study.